The Effect of Anesthetic Depth on the Occurrence of Emergence Delirium in Children Undergoing Strabismus Surgery: A Prospective Observational Study - Yea-Ji Lee; Jung-Won Hwang; Sang-Hwan Do; Hyo-Seok Na (Biomedicines)
Background/Objectives: Emergence delirium (ED) is one of the most frequent postoperative complications in pediatric patients after general anesthesia. In adults, a deeper intraoperative level of anesthesia has been reported as an independent predictor of postoperative delirium. However, the effect of anesthetic depth on ED has rarely been demonstrated in the pediatric population. We evaluated whether the depth of general anesthesia could affect the occurrence of emergence delirium (ED). Methods: Patients aged 3–5 years, scheduled for strabismus surgery were enrolled in this prospective observational study. Intraoperative bispectral index (BIS) was monitored, and the pediatric anesthesia emergence delirium (PAED) scale was evaluated. When the PAED scale was 10 or more, it was designated as an ED case. Results: According to the intraoperative mean BIS range, enrolled patients were divided into two groups: the low BIS (BIS < 40; n = 28) and the normal BIS (BIS 40–60; n = 34) group. The incidence of ED was comparable between the two groups (67.6% vs. 67.9%, odds ratio = 0.99, 95% CI = 0.34–2.89, p = 0.986). Conclusions: The intraoperative anesthetic depth did not seem to affect the occurrence of ED in pediatric patients undergoing strabismus surgery under general anesthesia. Future studies with a larger sample size are necessary for more authentic results.